The Importance of Location as a Determinant of Foreign Direct Investment : The African Continental Free Trade Area Agreement as a Model (A Theoretical Analytical Study) (Journal of Economic Additions, 2025)
This study highlights the role of location in attracting foreign direct investment (FDI) by reviewing key economic theories and examining the African Continental Free Trade Area (AfCFTA) as a model to enhance investment appeal. Using a deductive method with descriptive and analytical approaches, it addresses both theoretical and applied aspects. Findings show that a favorable business environment and high efficiency are key factors attracting multinational corporations. Many African AfCFTA members are implementing reforms to improve the investment climate. The study underscores shifts in FDI determinants in Africa and opportunities to strengthen the continent’s position in the global economy.Keywords: Location; Foreign Direct Investment; Multinational Enterprises African Continental Free Trade Area (AfCFTA)Jel Classification Codes: F21, F2, F23, F15
Keywords: Location; Foreign Direct Investment; Multinational Enterprises African Continental Free Trade Area (AfCFTA